Pendidikan Prenatal Yahudi dan Relevansinya dengan Pendidikan Islam - Mivtahul Kasana; Anggraeni Novita Sari (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This article attempts to analyze the relevance of Jewish prenatal education to Islamic education. This research uses descriptive-analysis method with content analysis approach on the book